👤

Answer :

Step-by-step explanation:

Given equation

  • P = 2a +4b

1. Rearrange it to make a the subject

  • P - 4b = 2a
  • 2a = P - 4b
  • a = (P/2) - (4b/2)
  • a = (P/2) - 2b

2. Rearrange it to make b the subject

  • P - 2a = 4b
  • 4b = P - 2a
  • b = (P/4) - (2a/4)
  • b = (P/4) - (a/2)

Answer:

see explanation

Step-by-step explanation:

(1)

P = 2a + 4b ( subtract 4b from both sides )

P - 4b = 2a ( isolate a by dividing both sides by 2 )

[tex]\frac{P-4b}{2}[/tex] = a

and

(2)

P = 2a + 4b ( subtract 2a from both sides )

P - 2a = 4b ( isolate b by dividing both sides by 4 )

[tex]\frac{P-2a}{4}[/tex] = b